'Forget it, Jake. It's Chinatown': The policing of Chinese organised crime in the UK. (March 2016) - Silverstone, Daniel; Whittle, Joe
This article outlines the impact and changing nature of Chinese organised crime in the United Kingdom (UK). It reviews the conventional policing approaches to the problem in the UK and in China, and argues they are limited in their scope and could be substantially improved. It suggests this is possible by employing police specialists here and in-country. The evidence for the paper has been collected from interviews with the relevant law enforcement and government personnel in the UK and in China in 2010 and again in 2014–15.